Primary Uterine Cervix Schwannoma: A Case Report and Review of the Literature. (20th December 2012) - Tahmasbi, Maryam; Nguyen, Johnny; Ghayouri, Masoumeh; Shan, Yuan; Hakam, Ardeshir
Abstract : Schwannoma (neurilemmoma) is a benign peripheral nerve sheath tumor that occurs in a wide variety of locations; however, its finding in the uterine cervix is extremely rare. We report a case of an incidental primary benign cervical schwannoma in a 48-year-old woman. In the English literature, a few cases of primary schwannoma of the cervix have been reported, which include seven cases of primary malignant cervical schwannoma and only two that are benign. These cases are reviewed in the following discussion.